Special Features of the Forming of Thermal Waters of the Eastern Part of the Khangay Neotectonic Uplift - Badminov, PS; Ganchimeg, D; Pisarsky, BI; Oyuntsetseg, D; Orgilyanov, GI; Kryukova, IG; Zundui-Osor, Ch (Proceedings of the Mongolian Academy of Sciences, 2011)
Khangay neotectonic uplift is a large block of the earth’s crust confined to the area between two sublatitudinal deep faults (Bulnay and Goby-Altay). They are active faults accommodating main compression stresses in contract to the extension existed in the other area of the Khangay uplift. In contrast to continental rift zones of Khangay it is the region of compression. It is area with the increased values of the heat flux. DOI: http://dx.doi.org/10.5564/pmas.v0i4.48 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.64-70